2016
DOI: 10.1007/s10616-016-9994-x
|View full text |Cite
|
Sign up to set email alerts
|

The bovine endometrial epithelial cells promote the differentiation of trophoblast stem-like cells to binucleate trophoblast cells

Abstract: Endometrial epithelial cells (EECs) cultured in vitro are valuable tools for investigating embryo implantation and trophoblast differentiation. In this study, we have established the bovine EECs and trophoblast stem-like (TS) coculture system, and used it to investigate the binucleate cell formation of ungulates. The EECs was derived from the uterine horn ipsilateral to the corpus luteum by using collagenase I and deoxyribonuclease I, which exhibited typical epithelial morphology and were expressing bovine ute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…We stablished an endometrial epithelial cell line in a manner that in every replicate, aliquots containing cells originated from the same pool were applied. Regarding the biological accuracy of our in vitro model, the co-expression of cytokeratin and vimentin in our BEEC line is in line with previous reports describing the expression of vimentin by cytokeratinpositive epithelial cells maintained in culture (Wang et al, 2000;Zeiler et al, 2007;Li et al, 2016) via a process described as epithelial-mesenchymal transition (Kalluri & Weinberg, 2009). However, even after three passages the BEECs displayed no changes on abundance of transcripts for epithelial-cell origin (KRT18) and functional markers (ESR1, IFNAR1 and PTGS2) rendering our BEEC line valid to address the aims of the study.…”
Section: Discussionsupporting
confidence: 88%
“…We stablished an endometrial epithelial cell line in a manner that in every replicate, aliquots containing cells originated from the same pool were applied. Regarding the biological accuracy of our in vitro model, the co-expression of cytokeratin and vimentin in our BEEC line is in line with previous reports describing the expression of vimentin by cytokeratinpositive epithelial cells maintained in culture (Wang et al, 2000;Zeiler et al, 2007;Li et al, 2016) via a process described as epithelial-mesenchymal transition (Kalluri & Weinberg, 2009). However, even after three passages the BEECs displayed no changes on abundance of transcripts for epithelial-cell origin (KRT18) and functional markers (ESR1, IFNAR1 and PTGS2) rendering our BEEC line valid to address the aims of the study.…”
Section: Discussionsupporting
confidence: 88%
“…Using a similar bovine endometrial cell isolation and culture technique as described here, Herath et al [46] reported epithelial and SF cell culture purities greater than 95% with undetectable levels of CD45 (common leukocyte antigen) mRNA and protein. Li et al [35] also reported that primary bovine endometrial epithelial cells did not exhibit significant changes in morphology or cell marker gene expression alterations after 20 passages. Similarly, we did not notice changes in the epithelial or SF cell morphology after multiple passages or days in culture.…”
Section: Discussionmentioning
confidence: 97%
“…Vimentin was detected within both cell types. Vimentin expression in isolated bovine endometrial epithelial cells has been reported and has been attributed to loss off cell to cell contact during isolation resulting in a limited epithelial to mesenchyme transition [35].…”
Section: Immunocytochemistry (Icc) Of Endometrial Cell Monoculturesmentioning
confidence: 99%
“…The former contained a greater proportion of endometrial stroma (VIM) and vascular cell (FLT1) markers than cytobrush samples (Johnson, Austin, Collins, Murdoch, & Hansen, ). Because of the more superficial sampling compared to biopsies, cytobrush samples were enriched in endometrial epithelial cells (KTR18) and immune cells (CD3D) markers (Li et al., ). It is unlike that either probing technique reached the myometrial layer, because abundance of MSTN was similar between groups.…”
Section: Discussionmentioning
confidence: 99%